2020
DOI: 10.4314/ujas.v19i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Field-based Evidence of the Black Coffee Twig Borer infesting Maesopsis eminii in Coffee Agro-systems in Kiboga District, Uganda

Abstract: Despite Ugandan coffee farmers’ preference for Maesopsis eminii as a shade tree, the species is an alternate host for the black coffee twig borer, Xylosandrus compactus (Eichhoff)—a major insect pest of coffee in the country. Wilting and drying of leaves and branches of young M. eminii trees (<5 m tall) observed in Kiboga District, Uganda. The branches were trimmed off the trees, separated into primary and secondary branches and then the percentage of those possessing characteristic X. compactus entry holes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Xylosandrus compactus is a serious pest of coffee in Hawaii (Greco and Wright, 2015), in India (Muthappa and Venkatasubbaiah, 1981;Ramesh, 1987) and in Uganda (Kagezi et al, 2014). It also caused economic damage to cacao in Uganda (Kagezi et al, 2014), tea in Japan (Kaneko et al, 1965), chestnut in China (Yan et al, 2001) and many other crops (EPPO, 2020).…”
Section: Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Xylosandrus compactus is a serious pest of coffee in Hawaii (Greco and Wright, 2015), in India (Muthappa and Venkatasubbaiah, 1981;Ramesh, 1987) and in Uganda (Kagezi et al, 2014). It also caused economic damage to cacao in Uganda (Kagezi et al, 2014), tea in Japan (Kaneko et al, 1965), chestnut in China (Yan et al, 2001) and many other crops (EPPO, 2020).…”
Section: Biologymentioning
confidence: 99%
“…Xylosandrus compactus is a serious pest of coffee in Hawaii (Greco and Wright, 2015), in India (Muthappa and Venkatasubbaiah, 1981;Ramesh, 1987) and in Uganda (Kagezi et al, 2014). It also caused economic damage to cacao in Uganda (Kagezi et al, 2014), tea in Japan (Kaneko et al, 1965), chestnut in China (Yan et al, 2001) and many other crops (EPPO, 2020). In Italy the pest severely affected Ceratonia siliqua, Laurus nobilis, Pistacia lentiscus, Quercus ilex, Ruscus aculeatus and Viburnum tinus (Garonna et al, 2012;Vannini et al, 2017;Gugliuzzo et al, 2020), Tilia platyphyllos (Faccoli, 2021) and occasionally found also on Cupressus sempervirens (Servizio Fitosanitario Regione Lazio, 2014).…”
Section: Biologymentioning
confidence: 99%
“…Xylosandrus compactus is a serious pest of coffee tree in Hawaii (Greco and Wright, 2015), in India (Muthappa and Venkatasubbaiah, 1981;Ramesh, 1987) and in Uganda (Kagezi et al, 2014). It also caused economic damage to cacao tree in Uganda (Kagezi et al, 2014), tea in Japan (Kaneko et al, 1965), chestnut in China (Yan et al, 2001) and many other crops (EPPO, 2020).…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Xylosandrus compactus is a serious pest of coffee tree in Hawaii (Greco and Wright, 2015), in India (Muthappa and Venkatasubbaiah, 1981;Ramesh, 1987) and in Uganda (Kagezi et al, 2014). It also caused economic damage to cacao tree in Uganda (Kagezi et al, 2014), tea in Japan (Kaneko et al, 1965), chestnut in China (Yan et al, 2001) and many other crops (EPPO, 2020). In Italy the pest severely affected Ceratonia siliqua, Laurus nobilis, Pistacia lentiscus, Quercus ilex, Ruscus aculeatus and Viburnum tinus (Garonna et al, 2012;Vannini et al, 2017;Gugliuzzo et al, 2020), Tilia platyphyllos (Faccoli, 2021) and was occasionally found also on Cupressus sempervirens (Servizio Fitosanitario Regione Lazio, 2014).…”
Section: Uncertaintiesmentioning
confidence: 99%
“…(Hara et al 1979, Bhat et al 1988, Oliveira et al 2008, Garonna et al 2012, Pennacchio et al 2012, Vannini et al 2017, Josep et al 2021, Urvois et al 2021). From an economic perspective, Kagezi et al (2013) estimated that 40.3% of Robusta coffee trees per farm were infested by X. compactus in Uganda in the year 2012, resulting in an annual foreign exchange loss of US$40 million based on the market prices and production volumes of that year.…”
Section: Introductionmentioning
confidence: 99%